Saint Kitts and Nevis. Significant achievements 2022 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
IICA partnered with other institutions to prepare a Green Climate Fund (GCF) Simplified Approval Process Concept Note for the St. Kitts and Nevis Climate Smart Agriculture Project; also involved training extension officers and farmers in greenhouse gas monitoring and record keeping. It collaborated to increase farmer participation in the Caribbean Climate Responsive Agriculture Forum and prioritized Agricultural Health and Food Safety, providing technical support for disease surveillance and detection, and successfully support the development of an urban farm and training center for persons with disabilities. It supported small and medium enterprises through various initiatives, including providing packing material and supporting trade efforts.